Media Use and Social Influence Among the Moravian Brethren in the Baltic Region with a Focus on Modern-Day Latvia - Gvido Straube (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer, 2023)
The Herrnhut Brethren (Moravians) expanded to the Baltic region in the early eighteenth century and quickly became a substantial religious force, especially among the local Estonian and Latvian peasant population. Instead of following a top-down institutional approach to Christianity, the Moravians approached the peasants as equals. The resulting religious contact between the Moravians and the Baltic Lutheran Church entrenched Christianity in the Baltic countryside more than had previously been the case and empowered the local population, largely through the innovative use of media and access to education.